Rules and reasoning : second International Joint Conference, RuleML+RR 2018, Luxembourg, Luxembourg, September 18-21, 2018, Proceedings /: second International Joint Conference, RuleML+RR 2018, Luxembourg, Luxembourg, September 18-21, 2018, Proceedings. (2018) - Unknown
No abstract available